Cutaneous Paecilomyces lilacinus infection mimicking cellulitis in an immunocompetent patient: Report of a case and review of the literature - Yen-Ta Chen; Chih-Chiang Chen (Wolters Kluwer Medknow Publications, 2016)
Paecilomyces lilacinus, a ubiquitous saprophytic mold found in the environment, is an emerging pathogen that causes localized to severe systemic diseases, especially in immunocompromised patients. Thus far, there are only eight reports on immunocompetent patients with cutaneous P. lilacinus in the English literature. We herein present the case of an 87-year-old immunocompetent Taiwanese man who presented with a progressive, tender, erythematous plaque mimicking cellulitis on the ventral surface of the right forearm for 2 weeks. The patient was initially diagnosed as a case of cellulitis; however, due to unresponsiveness to the treatment for 1 week, we decided to perform skin biopsy and tissue culture. Results of histopathologic analysis, tissue culture, and polymerase chain reaction assay indicated cutaneous P. lilacinus infection. Consequently, systemic antifungal treatment with oral itraconazole (200 mg/d) was initiated and the skin lesion resolved after a 4-week treatment.